Contributions From Psychology to Effectively Use, and Achieving Sexual Consent - Flecha, Ramon; Tomás, Gema; Vidu, Ana (Frontiers in Psychology, 2020)
Psychology related to areas such as gender, language, education and violence has provided scientific knowledge that is contributing to reducing coercive social relationships and to expanding freedom in sexual-affective relationships. Nonetheless, today there are new challenges that require additional developments. In the area of consent, professionals from the fields of law, gender, education and others, are in need of evidence about conditions in human communication that produce consent differentiating them from conditions that coerce. Up to now, consent has been focused on verbal language, for example, “no means no” or “anything less than yes is no”. Despite the fact that focusing consent on verbal language is a very important part of the problem, and has meant a huge advance, it does not solve most of the issues currently raised, like the famous case of “La Manada” in Spain. This article presents the most recent results of a new line of research, which places the problem and the solution in communicative acts, and not only in speech acts. Even though there might be a “yes” in a sexual-affective relationship, there might be no consent, and it is indeed a coercive relationship if that “yes” has been pronounced in a relationship determined by institutional power or by interactive power. Institutional power may occur if who made the proposal for the relationship is a person in charge of the process of selecting personnel in a company and one of the candidates is the person who received the proposal. Interactive power may occur if who makes the proposal is situated in an equal or inferior position for instance in the company to the person receiving it, but the former threatens to make sextortion to the latter. The potential social impact of this research has been already shown in the cases analyzed for this study.